Health needs: a conceptual and methodological review. (Revista Venezolana de Salud Pública, 2018)
The difficulty of accurately express the concept of health needs requires the review of the different positions in the conceptions about this construct, in order to conduct effective actions to meet these requirements when concerned. So we reviewed the literature of the subject and determine the ontological, epistemological and methodological prevalent to study and define health needs. To ensure identification of studies on the subject, it was made sure to consult only the publications of peer-reviewed journals and indexed in the area and presented in various databases. As a result of this recognition, it was studied a total of 26 articles, moreover twenty-three publications addressed the area of interest from the quantitative or positivist approach and three from the qualitative approach that tried to capture the complexity of the phenomenon. The variables more studied were employment status, age, place of origin and source of assistance to health services. For the analysis, descriptive statistics expressed as absolute frequencies or regression. We conclude that persist a positivist approach when studying the diverse in interpretation of human needs in health and well it is perceived that there is no consensus or standard that defines how to prioritize their assessment.
Keywords: Needs; health; concept; methodology